2002
DOI: 10.1093/oxfordjournals.molbev.a004146
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Slowed Rate of Molecular Evolution in the Order Acipenseriformes

Abstract: A test of the hypothesis that the members of the order Acipenseriformes (sturgeons and paddlefishes) possess a slowed rate of molecular evolution was carried out by conducting relative-rate comparisons with representatives of four groups of teleost fishes (Cypriniformes, Elopomorpha, Salmonidae, and Percomorpha) using 21 nuclear or mitochondrial protein loci and the nuclear and mitochondrial small subunit rRNA genes, obtained from the literature or our own research. In 70 out of 81 comparisons between individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 40 publications
3
59
0
4
Order By: Relevance
“…Ward et al (2009) showed that about 17% of the genetic divergence values among congeners are lower than 3% and 3.7% of the congeners' comparisons, which are lower than 1%, consistent with the three cases reported here. Krieger and Fuerst (2002) observed in their work that different teleost orders have different evolutionary rates and that it is possible that different families, genera, and species could have different evolutionary rates, which could explain the low values found in some pairs of species. Moreover, these low values may indicate a recent radiation for these species, as reflected by the low K2P divergences observed between pairs of species.…”
Section: Discussionmentioning
confidence: 94%
“…Ward et al (2009) showed that about 17% of the genetic divergence values among congeners are lower than 3% and 3.7% of the congeners' comparisons, which are lower than 1%, consistent with the three cases reported here. Krieger and Fuerst (2002) observed in their work that different teleost orders have different evolutionary rates and that it is possible that different families, genera, and species could have different evolutionary rates, which could explain the low values found in some pairs of species. Moreover, these low values may indicate a recent radiation for these species, as reflected by the low K2P divergences observed between pairs of species.…”
Section: Discussionmentioning
confidence: 94%
“…Sturgeons are considered as being among the most ancient actinopterygian fishes (51) and to have undergone remarkably little morphological change, indicating that their evolution has been exceptionally slow with a significant slower rate of molecular change than observed for most fish (52). The discovery, in Adriatic sturgeon, of a typical OC protein that has retained MGP features is consistent with the current theory that both OC and MGP share a common ancestral entity, with OC originating, through gene duplication and subsequent sequence divergence, from an ancestral MGP gene (7).…”
Section: Discussionmentioning
confidence: 99%
“…Values smaller than this average, such as those observed in the present work and in the above-cited papers, can be explained in two ways: the rate of evolution can vary among different higher taxa and, consequently, the accumulation of substitutions can vary. In fact, it has been observed that different teleost orders have different evolutionary rates (Krieger and Fuerst 2002). Another possible explanation could relate to species ages, where evolutionarily "young" species may not have had sufficient time to accumulate many mutations in their barcodes.…”
Section: Discussionmentioning
confidence: 99%